The cost of COVID-19 on the Indonesian economy: A Social Accounting Matrix (SAM) multiplier approach - Pradesha, Angga; Amaliah, Syarifah; Noegroho, Anang; Thurlow, James (International Food Policy Research Institute, 2020)
Sustained economic growth and a declining trend in poverty over the years in Indonesia potentially will come to a halt this year. This development cost comes as a result of the COVID-19 pandemic outbreak that recently hit the country. Like in many other countries, one of the largest costs of COVID-19 comes from the social distancing policy, which is a proven public health measure to reduce the spread of the virus by limiting people’s movements and interactions for a certain period of time. The government of Indonesia adopted this approach by gradually introducing in certain regions the Large-scale Social Restriction (PSBB) policy from early April 2020. PSBB restricts non-essential economic activities and people’s movement in order to contain the virus. IFPRI, the National Development Planning Agency of Indonesia (BAPPENAS), and IPB University used a SAM multiplier model to measure the economic impact of PSBB if restrictions were to be in place for four weeks and to explore potential recovery processes after the policy ends. Some of the key findings were: • National GDP is estimated to fall by 24 percent during the four-week PSBB period, • External sector shocks – reduced export demand, lower remittances, and lower foreign investments – contribute around one-third of total GDP losses; • The GDP of Indonesia’s agri-food system falls by 13 percent despite agriculture activities being excluded from restrictive measures; • National poverty is expected to jump by 13 percentage points – an additional 36 million people will fall into poverty during the four-week PSBB period; and • By the end of 2020, due to COVID-19 the annual GDP growth is expected to be between 5.3 and 7.3 percent lower than under a baseline scenario without COVID-19.